Dynamics of livestock production systems, drivers of change and prospects for animal genetic resources - Seré Rabé, Carlos; Zijpp, A.J. van der; Persley, Gabrielle J.; Rege, J.E.O. (Cambridge University Press, 2008)
This overview analyses the key drivers of change in the global livestock sector and assesses how they are influencing current trends and future prospects in the world's diverse livestock production systems and market chains; and what are their consequent impacts on the management of animal genetic resources for food and agriculture. The trends are occurring in both developing and industrialized countries, but the responses are different. In the developing world, the trends are affecting the ability of livestock to contribute to improving livelihoods and reducing poverty as well as the use of natural resources. In the industrialized world, the narrowing animal genetic resource base in industrial livestock production systems raises the need to maintain a broader range of animal genetic resources to be able to deal with future uncertainties, such as climate change and zoonotic diseases.This chapter discusses:• What are the global drivers of change for livestock systems? Economic development and globalization; changing market demands and the “livestock revolution”; environmental impacts including climate change; and science and technology trends.• How are the livestock production systems responding to the global drivers of change? Trends in the three main livestock production systems (industrial, crop-livestock and pastoral systems); the range and rate of changes occurring in different systems and how these affect animal genetic resources. The implications are that breeds cannot adapt in time to meet new circumstances. Hence new strategies and interventions are necessary to improve the management of animal genetic resources in situations where these genetic resources are most at risk.• What are the implications for animal genetic resources diversity and for future prospects of their use? - Industrial livestock production systems are expected to have a limited demand for biodiversity, while crop-livestock and pastoral systems will rely on biodiversity to produce genotypes of improved productivity under changing environmental and socio-economic conditions. All systems will rely on biodiversity, albeit to varying degrees, to cope with expected climate change.• What immediate steps are possible to improve animal genetic resources characterization, use and conservation? Appropriate institutional and policy frameworks are required to improve animal genetic resources management and these issues are being addressed at national and intergovernmental levels, in a process led by FAO to promote greater international collaboration on animal genetic resources. Based on an analysis of the current situation, the continuing loss of indigenous breeds and new developments in science and technology, there are several complementary actions that can begin to improve the management of animal genetic resources and maintain future options in an uncertain world.These are summarized here as:a. “Keep it on the hoof” - Encouraging the continuing sustainable use of traditional breeds and in situ conservation by providing market-driven incentives, public policy and This paper has benefited from inputs from several reviewers and other contributors, and we thank all for their thoughtful insights. We acknowledge the contributions of our colleagues at FAO, particularly Irene Hoffmann, Dafydd Pilling and Henning Steinfeld, and at the International Livestock Research Institute (ILRI): Ade Freeman, Mario Herrero, Olivier Hanotte, Steve Kemp, Sandy McClintock, Sara McClintock, Margaret MacDonald-Levy, Susan MacMillan, Grace Ndungu, An Notenbaert, Mwai Okeyo and Robin Reid. other support to enable livestock keepers to maintain genetic diversity in their livestock populations.b. “Move it or lose it” - Enabling access to and the safe movement of animal genetic resources within and between countries, regions and continents is a key factor in use, development and conservation of animal genetic resources globally.c. “Match breeds to environments” - Understanding the match between livestock populations, breeds and genes with the physical, biological and economic landscape. This “landscape livestock genomics” approach offers the means to predict the genotypes most appropriate to a given environment and, in the longer term, to understand the genetic basis of adaptation of the genotype to the environment.d. “Put some in the bank” — New technologies make ex situ, in vitro conservation of animal genetic resources feasible for critical situations and are a way to provide long-term insurance against future shocks.The multiple values, functions and consequences of livestock production systems and their rapid rate of change lead to divergent interests within and between countries. Conversely, the uncertainty about the implications of rapid, multifaceted global change for each livestock production system and the resulting future changes in the required genetic make-up of animal genetic resources make collective action to tackle conservation of animal genetic resources a long-term, global public good. Conserving animal genetic resources will not by itself solve these problems, but it is an important first step towards maintaining future options.Advances in science and the technology, in areas such as reproductive technology, genomics and spatial analysis, as well as progress in conceptualization of global public good production for the future management of animal genetic resources, should enable the international community to address both the short- and long-term challenges in innovative ways.